Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007112.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy (PRK) versus laser assisted in situ keratomileusis (LASIK) for hyperopia correction

Abstract: No robust, reliable conclusions could be reached, but the non-randomised trials reviewed appear to be in agreement that hyperopic-PRK and hyperopic-LASIK are of comparable efficacy. High quality, well-planned open RCTs are needed in order to obtain a robust clinical evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…These surgical options include laser-assisted in situ keratomileusis (LASIK), photorefractive keratectomy, or phakic intraocular lens implantation. 3 Femtosecond lenticule extraction (FLEx) is a relatively new refractive surgery procedure in which a femtosecond laser is used to create an intrastromal lenticule that is removed after lifting the flap, as first described in 2006. 4 , 5 The FLEx procedure was further modified by eliminating the need for a flap by dissecting and extracting the lenticule through a small incision, known as a small incision lenticule extraction (SMILE).…”
Section: Introductionmentioning
confidence: 99%
“…These surgical options include laser-assisted in situ keratomileusis (LASIK), photorefractive keratectomy, or phakic intraocular lens implantation. 3 Femtosecond lenticule extraction (FLEx) is a relatively new refractive surgery procedure in which a femtosecond laser is used to create an intrastromal lenticule that is removed after lifting the flap, as first described in 2006. 4 , 5 The FLEx procedure was further modified by eliminating the need for a flap by dissecting and extracting the lenticule through a small incision, known as a small incision lenticule extraction (SMILE).…”
Section: Introductionmentioning
confidence: 99%
“…However, PRK is not very desirable in hyperopic ablation as it has a risk of peripheral corneal scarring, haze, and hyperopic regression [9, 10]. On the other hand, LASIK has been shown to lead to satisfactory results in hyperopia and hyperopic or mixed astigmatism [11], and when compared to photorefractive keratectomy (PRK) for hyperopia, LASIK was also associated with a faster stabilization of refraction, less pain [12], and less hyperopic regression, but comparable efficacy [13].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to hyperopic surface excimer laser treatments, clinical studies using large diameter, greater than 6.50 mm optical zone ablations with modern laser platforms report excellent efficacy and safety indices, albeit with early overcorrection and delayed post‐operative refractive stabilisation of up to three to six months . There is a paucity of RCTs . In a recent Cochrane review no suitable RCTs comparing hyperopic PRK and LASIK could be identified; however, analysis of non‐randomised trials showed comparable efficacy.…”
Section: Surface Versus Flapmentioning
confidence: 99%
“…There is a paucity of RCTs . In a recent Cochrane review no suitable RCTs comparing hyperopic PRK and LASIK could be identified; however, analysis of non‐randomised trials showed comparable efficacy.…”
Section: Surface Versus Flapmentioning
confidence: 99%